Beautiful and Innocent - Maser, Verena (My University, 2015)
This study examines the relationship between media content, its production, and its reception in Japanese popular culture with the example of the so-called yuri ("lily") genre that centers on representations of intimate relationships between female characters. Based on contemporary genre theory, which posits that genres are not inherent properties of texts, the central question of this study is how the yuri genre is discursively produced in Japan. To examine this question, the study takes a variety of sources into consideration: Firstly, it discusses ten exemplary texts from the 1910s to 2010s that in the Japanese discourse on the yuri genre are deemed the milestone texts of the yuri genre's historical development (Hana monogatari, Otome no minato, Secret Love, Shiroi heya no futari, BishÅ jo senshi Sailor Moon, Maria-sama ga miteru, ShÅ jo Sect, Aoi hana, Yuru yuri, and Yuri danshi). Secondly, interviews with ten editors working for Japanese manga magazines shed light on their assessment of the yuri genre. Finally, the results of an online survey among Japanese fans of the yuri genre, which returned 1,352 completed questionnaires, question hitherto assumptions about the fans and their reasons for liking the yuri genre. The central argument of this study is that the yuri genre is for the most part constructed not through assignments on part of the genre's producers but through interpretations on part of the genre's fans. The intimacy portrayed in the texts ranges from "friendship" to "love," and often the ideas of "innocence" and "beauty" are emphasized. Nevertheless, the formation of the yuri genre occurs outside the bounds of the texts, most importantly in fan works, i.e. derivative texts created by fans. The actual content of the originals merely serves as a starting point for these interpretations. Located at the intersection of Japanese studies, cultural studies, media studies, and sociology, this study contributes to our understanding of contemporary Japanese popular culture by showing the mutual dependencies between media content, production, and reception. It provides a deeper look at these processes through first-hand accounts of both producers and fans of the yuri genre.

Diese Dissertation untersucht die Beziehung zwischen Medieninhalten, deren Produktion sowie deren Rezeption in der japanischen Populärkultur am Beispiel des sogenannten yuri ("Lilie") Genres, in dem intime Beziehungen zwischen weiblichen Figuren im Mittelpunkt stehen. Basierend auf der gegenwärtigen Genretheorie, welche davon ausgeht, dass Genres keine inhärenten Eigenschaften von Texten sind, ist die zentrale Frage dieser Studie, wie das yuri Genre in Japan diskursiv produziert wird. Um dieser Frage nachzugehen, werden eine Reihe von Quellen berücksichtigt: Erstens werden zehn exemplarische Texte von den 1910er bis 2010er Jahren diskutiert, die im japanischen Diskurs über das yuri Genre als Meilensteine seiner historischen Entwicklung angesehen werden (Hana monogatari, Otome no minato, Secret Love, Shiroi heya no futari, BishÅ jo senshi Sailor Moon, Maria-sama ga miteru, ShÅ jo Sect, Aoi hana, Yuru yuri, und Yuri danshi). Zweitens beleuchten Interviews mit zehn Redakteuren japanischer Manga-Magazine deren Ansichten zum yuri Genre. Schließlich stellen die Ergebnisse einer Online-Umfrage unter japanischen Fans des yuri Genres, welche 1.352 vollständige Fragebögen erbrachte, die bisherigen Annahmen über die Fans und die Gründe für deren Begeisterung für das yuri Genre infrage. Das zentrale Argument dieser Studie ist, dass das yuri Genre größtenteils nicht durch Zuordnungen seiner Produzenten geschaffen wird, sondern durch Interpretationen seiner Fans. Die in den Texten porträtierte Intimität reicht von "Freundschaft" bis hin zu "Liebe", und oft werden die Ideen von "Unschuld" und "Schönheit" betont. Nichtsdestotrotz findet die Formierung des yuri Genres außerhalb der Texte statt, wobei am bedeutendsten Fan-Arbeiten sind, d.h. von Fans geschaffene derivative Texte. Der tatsächliche Inhalt der Original ist lediglich Ausgangpunkt dieser Interpretationen. Diese Studie befindet sich an der Schnittstelle von Japanologie, Cultural Studies, Medienwissenschaft und Soziologie und trägt zu unserem Verständnis der gegenwärtigen japanischen Populärkultur bei, indem sie die gegenseitigen Abhängigkeiten zwischen medialen Inhalten, Produktion und Rezeption zeigt. Sie gibt einen tieferen Einblick in diese Prozesse durch Berichte von sowohl Produzenten als auch Fans des yuri Genres.
Female Same-Sex Intimacy in the Japanese Yuri Genre
Keywords: Medien; Kultur; Intimität; Homosexualität; Kunst; 952 Geschichte Japans; Anime; Japan; Pop-Kultur